2015
DOI: 10.1002/jbio.201500150
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of forward and backward Second Harmonic Generation images to probe the nanoscale structure of collagen within bone and cartilage

Abstract: Collagen ultrastructure plays a central role in the function of a wide range of connective tissues. Studying collagen structure at the microscopic scale is therefore of considerable interest to understand the mechanisms of tissue pathologies. Here, we use second harmonic generation microscopy to characterize collagen structure within bone and articular cartilage in human knees. We analyze the intensity dependence on polarization and discuss the differences between Forward and Backward images in both tissues. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 43 publications
(56 reference statements)
1
32
0
Order By: Relevance
“…Second-harmonic generation microscopy, capable of imaging intact unstained collagen fiber orientation and organization (Chen et al, 2012; Houle et al, 2015; Lilledahl et al, 2015), revealed regional variations in human TMJ disc fiber orientation and organization, similar to that reported for porcine TMJ discs using polarized light microscopy and scanning electron microscopy (Detamore and Athanasiou, 2003; Shi et al, 2013). In the central region of the disc, collagen fibers run predominately in the anteroposterior direction and were tightly bound, supporting a primary direction of stretching in the anteroposterior direction during joint articulation.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Second-harmonic generation microscopy, capable of imaging intact unstained collagen fiber orientation and organization (Chen et al, 2012; Houle et al, 2015; Lilledahl et al, 2015), revealed regional variations in human TMJ disc fiber orientation and organization, similar to that reported for porcine TMJ discs using polarized light microscopy and scanning electron microscopy (Detamore and Athanasiou, 2003; Shi et al, 2013). In the central region of the disc, collagen fibers run predominately in the anteroposterior direction and were tightly bound, supporting a primary direction of stretching in the anteroposterior direction during joint articulation.…”
Section: Discussionsupporting
confidence: 70%
“…To determine tissue microstructure, the superior surface of an intact human TMJ disc was imaged using second-harmonic generation microscopy (Chen et al, 2012; Houle et al, 2015; Lilledahl et al, 2015). The disc was dissected from a fresh-frozen 73-year-old female cadaver, frozen until use at −20 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SHG provides an intrinsic contrast specific to fibrillar collagen, in particular in the bone matrix 36–40 , and hence provides an image of the collagen matrix intrinsically registered with the THG image. The SHG signal depends on the degree of alignment and packing density of the collagen fibrils as well as their relative orientation with respect to the imaging plane and to the polarization of the excitation beam.…”
Section: Resultsmentioning
confidence: 99%
“…This methodology was capable to differentiate between cancerous and healthy tissue, with clear cut distinction between normal, benign, borderline, and malignant tumors of serous type. SHG was also applied to characterize collagen structure within bone and articular cartilage in human knees . This study analyzed the intensity dependence on polarization and discussed the differences between forward and backward images.…”
Section: Multiphoton Techniquesmentioning
confidence: 99%